2015
DOI: 10.20958/uis.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Ports and Digital Ports: The Narrative Construction and Social Imaginaries of the Island City of Mumbai

Abstract: Abstract:A city is a physical structure in one sense. In another sense, it is an organic body, poetically and metaphysically portrayed as having a soul. Most urban formations around the world, especially island cities, have a clear anthology of narratives that mesh the physical and the metaphysical of a city-body. The island city of Mumbai possesses characteristic socioeconomic traits have been counter-intuitively shaped by narratives and social imaginaries that would not have emerged if not for coastal featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Then, [16] highlighted the position of George Town as a creative city that can be a center of growth and progress to encourage economic development in Malaysia. Furthermore, [32] explained the influence of digital ports and ports on the socio-economic characteristics of Mumbai which were formed from a collection of seven islands which were physically joined through the reclamation process, construction of roads, trains, vehicles, and bridges.…”
Section: B Review Of Articles In Urban Island Studiesmentioning
confidence: 99%
“…Then, [16] highlighted the position of George Town as a creative city that can be a center of growth and progress to encourage economic development in Malaysia. Furthermore, [32] explained the influence of digital ports and ports on the socio-economic characteristics of Mumbai which were formed from a collection of seven islands which were physically joined through the reclamation process, construction of roads, trains, vehicles, and bridges.…”
Section: B Review Of Articles In Urban Island Studiesmentioning
confidence: 99%
“…Some scholars believe it does. Swaminathan's (2015) interpretation of the identity construction of the island city of Mumbai through the city's abundance of narratives and social imaginaries is a case in point. Swaminathan's overall presupposition is that a city is both a "physical structure" and an "organic body," which is "poetically and metaphysically portrayed as having a soul" (Swaminathan, 2015, p. 35).…”
Section: Do These Discourses Produce An Organic Collective Self?mentioning
confidence: 99%
“…Adam Grydehøj (2015aGrydehøj ( , 2015b has demonstrated that island and archipelago spatiality have a strong effect on urbanisation processes and that, under certain geographical conditions, such spatiality can foster the development of very dense and very large cities. Other scholars have used the concept of island cities as a means of understanding the effects of islandness in urban environments, of seeing how the 'island lure' functions even in centres of economic, political, and cultural power (e.g., Swaminathan, 2015;Steyn, 2015;Casagrande, 2016;Su, 2017).…”
Section: Current Trends In International Island Studiesmentioning
confidence: 99%